Understanding the environment worldviews of Malaysian project managers - Leby Lau, Jasmine; Hashim, Ahmad Hariza; Abu Samah, Asnarulkhadi; Salim Syed Salim, Azizah (Emerald Group Publishing, 2016)
Purpose – The purpose of this paper is to examine the dimensionality of the environmental concern scale (NEP) and to understand the environmental worldviews of Malaysian project managers.